The Effect of Progressive Muscle Relaxation Therapy and Deep Breath Relaxation on Lowering Blood Pressure in Hypertension Patients in Selajambe Village, Selajambe District, Kuningan Regency in 2024 - Rastipiati, Rastipiati; Nugraha, Moch. Didik; Nur Alifah, Dea (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Hypertension is a disease that causes premature death in the world. West Java Province ranks second with the most hypertension patients with a prevalence of 39.60%. Treatment of hypertension uses pharmacological therapy which can be combined with non-pharmacological therapies such as relaxation therapy. Currently, the belief of hypertension sufferers in chemical drugs is decreasing, and increasing treatment using complementary therapies. This study aims to determine the effect of progressive muscle relaxation therapy and deep breath relaxation on reducing high blood pressure in hypertensive patients in Selajambe village, Kuningan Regency, 2024. Method: This type of research is an analytic quasy experiment design with pre-test and post-test design. The population was 168 hypertensive patients with purposive sampling technique. Bivariate analysis using the T test. Result: The results showed that the average blood pressure before being given progressive muscle relaxation was 160.1/101.7mmHG which decreased to 135.6/79.35. The results of deep breath relaxation were 155.9/95.20mmHg decreased to 147.0/87.20mmHg. T test on progressive muscle relaxation obtained p-value = 0.000 on systole blood pressure and p-value = 0.006 on diastole blood pressure. The results of deep breath relaxation obtained p-value = 0.011 on systole blood pressure and p-value = 0.002 on diastole blood pressure (<0.05). Conclusion: There is an effect of progressive muscle relaxation therapy and deep breath relaxation on reducing high blood pressure in hypertensive patients in Selajambe village, Kuningan Regency, 2024. Hypertensive patients can combine drug therapy and relaxation as part of controlling blood pressure.